New conditions for the exponential stability of fractionally perturbed ODEs - Milan Medved (Electronic Journal of Qualitative Theory of Differential Equations, 2018)
The aim of this paper is to present some results on the exponential stability of the zero solution for a class of fractionally perturbed ordinary differential equations, whose right-hand sides involve the Riemann–Liouville substantial fractional integrals of different orders and we assume that they are polynomially bounded. In their proofs we apply a method recently developed by Rigoberto Medina. We also prove an existence result for this type of equations.